2020
DOI: 10.1101/2020.08.05.238105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epitomic analysis of the specificity of conformation-dependent, anti-Aß amyloid monoclonal antibodies

Abstract: Antibodies against Aß amyloid are indispensable research tools and potential therapeutics for Alzheimer’s Disease, but display unusual properties, such as specificity for aggregated forms of the peptide, ability to distinguish several polymorphic aggregate structures and ability to recognize generic aggregation-related epitopes formed by unrelated amyloid sequences. Understanding the mechanisms underlying these unusual properties of anti-amyloid antibodies and the structures of their corresponding epitopes is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…To profile the development of A␤ aggregates across the lifespan of 3xTg AD-model mice, we performed immunostaining of brain sections using 6E10, an antibody that recognizes exposed residues 5-7 of the human A␤ peptide [51], and mOC78 antibodies that recognize a conformational epitope at positions 8-11 and 24-26 [52] of aggregates of oligomeric mouse and human A␤ peptide and other amyloids [7]. We examined the staining of large aggregates and plaques (>80 m 2 ) in CA1 of the hippocampus, a region that is known to be affected early in AD [53].…”
Section: Large Extracellular Aβ In the Ca1 Subregion Of The 3xtg-ad M...mentioning
confidence: 99%
“…To profile the development of A␤ aggregates across the lifespan of 3xTg AD-model mice, we performed immunostaining of brain sections using 6E10, an antibody that recognizes exposed residues 5-7 of the human A␤ peptide [51], and mOC78 antibodies that recognize a conformational epitope at positions 8-11 and 24-26 [52] of aggregates of oligomeric mouse and human A␤ peptide and other amyloids [7]. We examined the staining of large aggregates and plaques (>80 m 2 ) in CA1 of the hippocampus, a region that is known to be affected early in AD [53].…”
Section: Large Extracellular Aβ In the Ca1 Subregion Of The 3xtg-ad M...mentioning
confidence: 99%
“…Immunostaining with anti-Pum antibody showed that stalled NPCs were localized to the perinuclear ER compartment where some of them colocalized with the conformation-specific mOC78 antibody (Fig. 2e), which recognizes a discontinuous epitope consisting of residues 8-12 (SGYEV) and 24-26 (VGS) in misfolded or aggregated Aβ [55,56], suggesting that stalled NPCs adopted abnormal conformation and represented aberrant APP.C99 species. Thus, the translation of APP.C99 is stalled at two sites: one at or near the stop codon, another at an internal site ~ 30 AA upstream of the stop codon based on the size of the lower band.…”
Section: Er-associated Stalled Translation Of Appc99mentioning
confidence: 99%
“…have been obtained successfully by using specific antibodies to screen phage display library combined with gene sequencing. These studies demonstrated that the obtained epitopes/mimotopes could be linear or conformational [11,18,20], and that these epitopes/ mimotopes were feasible for serological diagnosis and vaccine [10], and were more specific and sensitive [21,22]. However, there were few reports on the use of the phage display technique in the field of infertility.…”
Section: Mots-clésmentioning
confidence: 99%